2015
DOI: 10.1186/1471-2490-15-4
|View full text |Cite
|
Sign up to set email alerts
|

Spleen injury following left extracorporeal shockwave lithotripsy (ESWL)

Abstract: BackgroundA splenic rupture associated with extracorporeal shockwave lithotripsy (ESWL) is exceedingly rare. We report a case of stage 3 splenic laceration, hemoperitoneum and subsequent splenic rupture following an ESWL for a left mid polar renal calculus.Case presentationDuring the ESWL, although the patient’s pain was controlled the gentleman was very nervous and had to be repositioned eight individual times.Approximately 6 hours after the ESWL, the patient phoned the urologist complaining of severe left fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Sarcosine has previously been reported to be associated with prostate cancer 26 , but subsequent studies showed no association with aggressiveness 42 43 44 . In our study, sarcosine was detected in high abundance.…”
Section: Discussionmentioning
confidence: 98%
“…Sarcosine has previously been reported to be associated with prostate cancer 26 , but subsequent studies showed no association with aggressiveness 42 43 44 . In our study, sarcosine was detected in high abundance.…”
Section: Discussionmentioning
confidence: 98%
“…However, the phenomenon of splenic rupture secondary to trauma caused by ESWL is an exceptional occurrence [1]. On a worldwide literature search, there have been only 11 published cases of splenic injury associated with ESWL since the inception of the shock wave technology in 1980 [10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…After ESWL was implemented it was supposed that 85% of all patients with kidneys stones could be cured by nonsurgical means [10]. The initial promising results of ESWL were challenge with common side effects caused by this procedure, such as bleeding, severe pain, or urinary tract infections [9], rare complications, such as spleen rupture or intrarenal hematoma [11,12,13], and long-term medical effects: hypertension and diabetes mellitus [14,15,16].…”
Section: Kidney Stone Diseasementioning
confidence: 99%